Bilateral Irreversible Blindness Following Urine Therapy to the Eyes - Christianah Olufunmilayo, Fadamiro (Pakistan Journal of Ophthalmology, 2018)
This is a case report of a 36-year-old Nigerian photographer who suffered irreversible blindness following the use of urine as therapy for red eyes, the aftermath was devastating to the eyes, despite the resultant visual loss, and the eyes were disfigured due to bilateral anterior staphyloma. This is an avoidable case of blindness due to use of toxic agent on the eyes and calls for need of public enlightenment and eye health education on the use of self remedies for eye ailments and its untoward effects. Keywords: Blindness, Urine therapy, self-remedy.